Decolouration of Dye in Wastewater by Selected Fungal and Bacterial Species: A Bioremediation Approach - O B, Akpor; C O, Aipoh; A P, Olalekan (International Journal of Natural Sciences Research, 2014)
The objective of this investigation was to ascertain the dye decolouration ability of selected bacterial (Escherichia coli and Pseudomonas aeruginosa) and (Aspergillus niger and Aspergillus flavus) species in wastewater. The study was carried out under shake flasks conditions. After inoculation with the respective isolates, aliquot wastewater samples were aseptically removed from each flask, prior inoculation and every 24 h for the next 96 h for the estimation of dye concentration, using standard procedures. The results revealed optimum temperature for dye decolouration in the presence of the test isolates to range from 25 °C to 35 °C. A pH of 6 and 10 was observed to enhance dye by the bacterial species while 8 and 10 were observed to be optimum for the fungal species. At the different concentrations of sodium acetate used for investigation, 5 g/L was observed to be optimum, a trend that was observed in the presence of all the isolates. Among the different external carbon sources used for investigation, the study revealed methanol as the ideal external carbon source that enhanced dye decolouration by the isolates. With respect to nitrogen source, maximum decolouration was observed with yeast extract source, in the presence of the Aspergillus niger, Aspergillus flavus and Pseudomonas aeruginosa. None of the concentrations of peptone used for investigation enhanced decolouration by the test isolates. This trend was also irrespective of the isolate used for investigation. The study was able to reveal the effect of temperature the optimum temperature, pH, sodium acetate and peptone concentrations and carbon and nitrogen sources in the declaration of decolouration of the test dye in wastewater by the microbial species used for the investigation.